Respuesta :
Answer:
x = -5, y = -1
Step-by-step explanation:
You're given 2 equations:
-6x + 7y = 23
-5x + y = 24
you choose the equation that is easier to isolate a single variable to use as your substitution. I chose -5x + y = 24 because the 'y' is already by itself. Now solve for 'y'.
-5x + y = 24
y = 24 + 5x
Use this y-value to substitute into your other equation
-6x + 7y = 23
-6x + 7(24 + 5x) = 23
-6x + 168 + 35x = 23
29x = 23 - 168
29x = -145
x = -5
We found the value of 'x', so plug it back in to any of the two given equation to solve for y.
-5x + y = 24
-5(-5) + y = 24
25 + y = 24
y = 24 - 25
y = -1
Answer:
(-5,-1)
Step-by-step explanation:
First you must get a variable on one side alone. For example I done Y on the 2nd one. So to move it, you would take the 5x and move/add to the other side so Y=5x+24.
Then the substitution comes in. So you take
-6x+7(5x+24)=23 so you would plug in what Y equals. Then after you distribute the seven you would combine like terms. Then you take and move/subtract 168 from 23 which equals -145. Then you would divide by the number attached to the variable which is 29, therefore giving you x=-5
Then to get Y you simply plug what X equals into the X space.
Y=5(-5)+24
Y= -25+24
Y=-1
![Ver imagen music4me4life04](https://us-static.z-dn.net/files/d90/5c79e09c4439201beaf0e1782108f400.jpg)